1995
DOI: 10.1056/nejm199501053320103
|View full text |Cite
|
Sign up to set email alerts
|

Association of Epstein–Barr Virus with Leiomyosarcomas in Young People with AIDS

Abstract: EBV can infect smooth-muscle cells, at least in patients with AIDS, and it may contribute to the pathogenesis of leiomyomas and leiomyosarcomas in children with AIDS. EBV seems to play no part in smooth-muscle tumors in HIV-negative children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
336
2
9

Year Published

1995
1995
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 577 publications
(361 citation statements)
references
References 28 publications
14
336
2
9
Order By: Relevance
“…Furthermore, some follicular dendritic cells were successfully infected with EBV in vitro (38). Recently, smooth muscle tumors in either immunosuppressed AIDS patients or recipients of liver transplant were found to be EBV infected (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some follicular dendritic cells were successfully infected with EBV in vitro (38). Recently, smooth muscle tumors in either immunosuppressed AIDS patients or recipients of liver transplant were found to be EBV infected (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…The smooth muscle tumors can occur in peripheral soft tissue, intracranial space, or visceral sites, and tumor multiplicity is common. [76][77][78][79][80][81][82][83][84][85] Molecular genetic analysis has shown that multiple tumor represent independent clones rather than dissemination of a single neoplastic clone. 85 In multiple tumor cases, tumors arising in the transplant are of donor cell origin, whereas those at the other sites arise from recipient cells, which also points to polyclonal origin of multiple tumors.…”
Section: Ebv-associated Smooth Muscle Tumorsmentioning
confidence: 99%
“…1 EBV infection and consistent presence of EBV genome are associated with numerous malignant diseases, including African Burkitt lymphomas, 2 Hodgkin disease, 3 nasopharyngeal carcinoma (NPC), 4,5 leiomyosarcomas, 6 AIDS-associated central nervous system lymphomas, 7 T-cell lymphomas, 8 some gastric carcinomas, 9,10 breast cancers, 11 liver cancers, 12 lung cancers, colon cancers and prostate cancers. 13 In addition, post-transplant lymphoproliferative disorder (PTLD), one of the most dreaded complications in immunosuppressed organ allograft recipients is also a frequent problem due to EBV infection.…”
Section: Introductionmentioning
confidence: 99%